Comparative localization of cystathionine beta synthases and cystathionine gamma lyase in canine, non-human primate and human retina - Badiei, Alireza (Exp Eye Res, 2019)
Chronic exposure of the retina to light and high concentrations of polyunsaturated fatty acid in photoreceptor cells make this tissue susceptible to oxidative damage. As retinal degenerative diseases are associated with photoreceptor degeneration, the antioxidant activity of both hydrogen sulfide (H(2)S) and glutathione (GSH) may play an important role in ameliorating disease progression. H(2)S production is driven by cystathionine-γ-lyase (CSE) and cystathionine β–synthase (CBS), the key enzymes that also drive transsulfuration pathway (TSP) necessary for GSH production. As it is currently unclear whether localized production of either H(2)S or GSH contributes to retinal homeostasis, we undertook a comparative analysis of CBS and CSE expression in canine, non-human primates (NHP) and human retinas to determine if these antioxidants could play a regulatory role in age-related or disease-associated retinal degeneration. Retinas from normal dogs, NHPs and humans were used for the study. Laser capture microdissection (LCM) was performed to isolate individual layers of the canine retina and analyze CBS and CSE gene expression by qRT-PCR. Immunohistochemistry and western blotting were performed for CBS and CSE labeling and protein expression in dog, NHP, and human retina, respectively. Using qRT-PCR, western blot, and immunohistochemistry (IHC), we showed that CBS and CSE are expressed in the canine, NHP, and human retina. IHC results from canine retina demonstrated increased expression levels of CBS but not CSE with post-developmental aging. IHC results also showed non-overlapping localization of both proteins with CBS presenting in rods, amacrine, horizontal, and nerve fiber cell layers while CSE was expressed by RPE, cones and Mϋller cells. Finally, we demonstrated that these enzymes localized to all three layers of canine, NHP and human retina: photoreceptors, outer plexiform layer (OPL) and notably in the ganglion cells layer/nerve fiber layer (GCL/NFL). QRT-PCR performed using RNA extracted from tissues isolated from these cell layers using laser captured microdissection (LCM) confirmed that each of CBS and CSE are expressed equally in these three layers. Together, these findings reveal that CSE and CBS are expressed in the retina, thereby supporting further studies to determine the role of H(2)S and these proteins in oxidative stress and apoptosis in retinal degenerative diseases.